Rethinking Artisanal Mining: The Lived Experiences of Rural Artisanal Mining Communities in South Africa - Nonkululeko Melody Zondo (Journal of Social and Development Sciences, 2024)
In South Africa, colonialism and apartheid have left a legacy of a gendered, racially and geographically skewed extractive industry, in which many rural communities endowed with mineral resources face severe economic hardships, marginalization, and socio-cultural disorganization resulting from, among other things, land and mineral resource dispossession. Drawing on a broader doctoral study, this paper seeks to demonstrate the heterogeneity of artisanal mining practices as a response to many calls made by various scholars that there remains a need for greater attention to the complex social, economic and environmental factors underpinning the sector, especially in the South African context. It sheds light on the contextual nature of artisanal mining practices and the lived experiences of artisanal miners in rural South Africa. The study is qualitative in nature and is based on field research that includes in-depth interviews, site observations, and oral histories. Findings indicate that the marginalization of artisanal mining practices in South Africa stems from the history of mineral resources, land dispossession and displacement of indigenous mining practices. As a result, the study highlights the need to delve deeper into the contextualized land and mineral resource struggles and gendered and racialized dynamics that contribute to the marginalization of artisanal mining practices.